Nanoscale elemental quantification in heterostructured SiGe nanowires1. Issue 18 (14th May 2015) - Hourani, W.; Periwal, P.; Bassani, F.; Baron, T.; Patriarche, G.; Martinez, E.
<x xml:space="preserve">Abstract</x> Scanning Auger microscopy is used to determine the axial and radial chemical compositions of heterostructured Si1−xGex nanowires at the nanoscale.